COUNTRY RISK ANALYSIS FOR THE DEVELOPMENT OF GREEN HYDROGEN ECOSYSTEM: CASE STUDY OF LANDLOCKED COUNTRIES - Nuraliyeva Komila Sanakulovna (Web of Journals Publishing, 2025)
The global pursuit of decarbonization has elevated green hydrogen as a critical component of the future energy mix. While many coastal nations are rapidly advancing green hydrogen projects, landlocked countries face a distinct set of barriers that hinder their participation in this emerging market. These include challenges related to transport logistics, infrastructure limitations, water scarcity, and geopolitical dependencies. This paper provides a country risk analysis for the development of green hydrogen ecosystems in landlocked nations, focusing on Central Asia and selected African states. Using a multi-criteria framework combining PESTLE and SWOT analysis, the study identifies key risk factors—political, economic, environmental, and technological—and proposes strategic pathways to mitigate these risks. The findings highlight the need for regional cooperation, tailored investment models, and integrated policy reforms to enable landlocked countries to harness the potential of green hydrogen for sustainable development.
Keywords: Green hydrogen, country risk analysis, landlocked countries, renewable energy, sustainable development, hydrogen infrastructure, energy policy, PESTLE analysis, Central Asia, water scarcity.